Development of Website-Based Office Documentation Media Information System - Fadhel Ramadhanny; Muhammad Yusuf Nashirulhaq; Rina Kurniawati (Politeknik Piksi Ganesha Indonesia, 2022)
This application is a form of development of the existing applications. Office Documentation Application is designed to store and document all activities of employees in and outside the office. In designing and developing this application, the study applied the waterfall method; then, the Javascript programming language was for the appearance, and the PHP and Mysql programming languages were for database processing. To make the application display more efficient, the researchers redeveloped this Office Document application to make it more optimal when used, both in terms of appearance and more complex functions. So, it is hoped that with the development of the Office Document application, users can get a new experience when using this application, followed by a better look and function.